Telementoring in the K-12 classroom online communication technologies for learning - Scigliano, Deborah A., 1951-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book provides the latest research and the best practices in the field of telementoring, including provide guidance to professionals wanting to implement and improve their telementoring processes"--Provided by publisher.
1. Designs for curriculum-based telementoring / Judi Harris -- 2. Dimensions of design in K-12 telementoring programs / Kevin O'Neill -- 3. Telementoring and project-based learning / Joyce Yukawa -- 4. You had to be there / Kevin O'Neill, Sheryl Guloy -- 5. The transformative capacity of telementoring on self-efficacy beliefs / Deborah Scigliano -- 6. Fully including students, teachers, and administrators with disabilities in telementoring / Sheryl Burgstahler, Terrill Thompson -- 7. Electronic mentoring in the classroom / Carmit-Noa Shpigelman, Shunit Reiter -- 8. Meeting the needs of adolescents and young adults with disabilities / Katharine Hill, Joe Timmons, Christen Opsal -- 9. Telementoring in teacher education / Sandy Watson -- 10. Virtual mentoring / Thomas Peters, Terrie Dew -- 11. Telementoring and virtual professional development / Matthew Maurer -- 12. An orientation to Web 2.0 tools for telementoring / Robin Hastings -- 13. Web 2.0 for tele-mentoring / Shari Smith, Najmuddin Shaik, Emily Boles.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed Nov. 15, 2010).
Keywords: Mentoring in education -- Technological innovations; Mentoring -- Technological innovations; Telementoring programs; Project-based learning; Telementoring relationships; Construction of knowledge; Online environments; Telementoring benefits and limitations; Software design; Role of the subject matter expert; Role of the online facilitator; Synchronous and asynchronous communication; Electronic books